Driving sustainability to business success : the DS factor management system integration and automation - Pilot, Jayne. (Wiley corporate F&A series, 2015)
"Efficient, compliant management systems pave the road to sustainability through integration and automationThe book addresses the many definitions of sustainability and why CEOs need the links between sustainability, business value, and performance. Business leaders are committed to leading the way, and the book outlines the support of a management system structure and business principles that will drive the accomplishment of their mission. Stakeholder demands on CEOs include many challenges. Investors are assessing companies for financial performance. The shrinking talent pool of employees is looking to work with organizations that support social, environment, and economic operating practices and principles.Great leaders are those that ask questions, who are creative to drive innovation for growth of their company. The Assess-Reflect-Act section on international business principles defined in the book will ask you as the leader thought provoking questions to stimulate action within your organization to bring people, processes, and technology together for business success.Leaders need to transition to smart decisions that are data driven. The company's management system structure is important to build a strong framework for business process operations and automation for global competitiveness. Topics include: Business plans vs management systems Management system frameworks: standardization, ISO standards.